Effect of planting geometry and fertilizer levels on Yellow Sarson (Brassica rapa var. trilocularis) under rainfed condition (Journal of Oilseed Brassica, 2026)
A field experiment on different planting geometries viz., uniform row at 20, and 30 cm apart (G1 and G2), border row (3:1) at 20, and 30 cm apart (G3 and G4), and border row at 20 and 30 cm, and replacement with coriander in skipped row (G5 and G6) along with two levels of fertilizers (60-30-30 (F1), and 90-45-45 (F2) N, P2O5, and K2O kg/ha) carried out during Rabi, 2011-2012 at Assam Agricultural University, Jorhat, India revealed that different growth, and yield attributes except for 1000 seed weight, border row spaced at 20 cm, and replacement with coriander in the skipped row (G5) proved to be superior in comparison to other planting geometries. In case of seed yield, the highest value was recorded for border method spaced at 20 cm rows (G3). However, the stover yield was highest with uniform row spaced at 20 cm (G1). Highest oil content and oil yield was recorded in case of G3. The two levels of fertilizer did not influence plant characters. Though, the lower level of fertilizers (F1) recorded higher oil content but the oil yield was recorded higher with the higher level (F2). Higher uptake values of N, P, and K were recorded with planting geometry, G5, and with higher level of fertilizers (F2). In terms of benefit; cost ratio, border method spaced at 20 cm (G3) with lower level of fertilizers (F1) was found to be better than other treatments.